Sistem Pengambilan Keputusan Desain Menu Website PLN Batam Perspektif User - Heri Nuryanto (Computer Based Information System Journal, 2014)
series of problems faced by both the criteria and the alternatives. AHP can be used to solve problems that are complex to perform pembotan priority. By using the AHP, the evaluation and assessment activities to content published by PLN Batam can be done, it aims to determine what type ll interest to the reader so that the management web e-bright maximum of PLN Batam can be. So this method can also be used as an alternative in evaluating the management of web e-bright PLN Batam which has not been done. Based on the results of research and discussion is done, it can be concluded that: The percentage weighting for content published on the website in the e-bright PLN Batam is the largest horizontal menu by 25,6% and the percentage in weight for the content published on the website e-bright PLN This is the smallest Batam Us 2.4%